Resilient Infrastructure for Thriving Firms : A Review of The Evidence - Braese, Johannes; Rentschler, Jun; Hallegatte, Stephane (World Bank, Washington, DC, 2019)
This review examines the literature on the role of infrastructure in determining the productivity and competitiveness of firms. It shows that the existing evidence base is clear in concluding that reliable and high-quality infrastructure is a crucial foundation for enabling businesses to thrive. It demonstrates that the provision of electricity, transport, water, and telecommunications systems increases firm-level productivity. It also shows that providing infrastructure per se is not enough to boost productivity, unless it offers reliable service. Disruptions and irregular service have substantial adverse effects on firms, not least due to disrupted supply chains, underutilization of production capacity, and costly adaptation measures.